Benefits and challenges in adopting social media for SMEs: A case from Bangladesh - Pervin, Most. Tahura; Sarker, Bipul Kumar (Goodwood Publishing, 2021)
Purpose: The purpose of this study was to identify the challenges, Benefits, and various determinants which play an important role in adopting social media among small and medium-sized enterprises (SMEs) in Bangladesh, based on the (Technology-Organization-Environment) TOE Model. The TOE framework seeks to understand the significant factors influencing the decision to adopt social media in SMEs in Bangladesh. Research methodology: In the study, a random sampling method was used to select a representative sample from the existing active SMEs in different regions of Bangladesh. A structured questionnaire was designed to measure constructs such as relative advantage. Preliminary data were collected from 365 small and medium enterprises through field studies. Then the survey data were analyzed using logistic regression (L.R.) of the independent variables included in the TOE framework Results: The outcomes of the study found that only 5 variables: relative advantage, complexity, consistency, top management's assistance, and innovative management factors significantly influence SMEs' decisions to adopt social media. Limitations: The busy schedules of the respondents are key limitations for the study along with the study area. If the study could explore more districts besides Dhaka city, then the study outcomes would be more extensive. Contribution: The results from this study will help SME foundations, research institutes, and government policymakers to formulate strategies for optimal use of social media in SMEs.